The Personality Transformation of Lestari in Tenderlova’s Meant 2 Be: An Analysis through Allport’s Trait Theory - Puspita Rahmawati (Yayasan Darussalam Bengkulu, 2025)
This study investigates the personality development of the protagonists in Tenderlova’s Meant 2 Be by applying Allport’s trait theory, which classifies personality into traits, attitudes, and intentions. The research was conducted using a qualitative descriptive design with a library research approach, in which textual evidence from the novel was systematically analyzed and triangulated with relevant scholarly sources to ensure interpretive validity. The findings reveal that Lestari is initially characterized by insecurity, introversion, and sarcasm, yet also demonstrates kindness and empathy, while Adinata displays perseverance, humor, creativity, and affection but struggles with impulsivity. As the narrative progresses, both characters undergo significant transformation: Lestari becomes more open and emotionally resilient, whereas Adinata evolves into a more stable and caring figure. These results affirm Allport’s proposition that personality is a dynamic construct shaped by the interaction between individual dispositions and social environments. The discussion highlights how this novel contributes to broader understandings of identity formation in contemporary Indonesian youth literature and demonstrates the analytical value of applying trait-based psychology to popular fiction. The novelty of this study lies in extending Allport’s framework to a modern Indonesian novel rarely explored in prior research, thereby bridging literary psychology and cultural studies. The implications suggest that such an approach can enrich literary pedagogy by fostering empathy, critical engagement, and psychological awareness in the study of fiction, while also informing future comparative analyses across diverse literary works.